Delphi study on the metaverse as an appropriate setting for mental health care: conceptualization, opportunities, challenges, and conditions - Gloeckler, Sophie; Ford, T. J.; Biller-Andorno, Nikola (Frontiers in Virtual Reality, 2025)
BackgroundMetaverse-based mental health services may be poised to increase access and augment treatment; doing so ethically requires anticipating risks and actively shaping how this emerging setting might support care. With limited means to directly evaluate the Metaverse’s potential role in the provision of appropriate mental health care, there is value in conceptual expert input.MethodsThe aim of the present Delphi study was to gather global academic experts to explore where opinions converged and diverged regarding three foundational topics: 1) A working definition of the Metaverse; 2) A conception of appropriate care in the Metaverse that identifies key potential challenges; and 3) Conditions that may help align mental health offerings in the Metaverse with tenets of appropriate care. The study was carried out in an e-Delphi format–asynchronously online–in three rounds with statements divided according to the study aims. Panelists rated agreement with statements, suggested modifications, provided commentary on their position, suggested additional statements, and reviewed panelist-generated statements.ResultsThe 14 panelists, identified through literature review, represented top universities and pioneering research labs in the field. Of the 27 original statements, all reached consensus by Round Three. 27 new statements were generated based on panel suggestion, of which 20 reached consensus. Panelists produced a working definition of the Metaverse, exhibited clarity regarding the possible suitability of the Metaverse as a setting for appropriate mental healthcare, identified challenges to providing such care, and identified interventions that may meaningfully address Metaverse-specific care concerns.ConclusionAdditional research building on the identified issues and solutions is needed to responsibly shape the form and content of both future mental health offerings and the Metaverse itself. Next steps should involve service users to voice their perspective; clinicians to shape best clinical practice; industry to consider standards; and policymakers to build upon the suggested regulatory measures.